2015
DOI: 10.1590/s1677-5538.ibju.2013.00186
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes caused by meclofenamic acid in androgen independent prostate cancer tumors: evaluation in a mouse model

Abstract: Meclofenamic acid is a nonsteroidal anti-inflammatory drug that has shown therapeutic potential for different types of cancers, including androgen-independent prostate neoplasms. The antitumor effect of diverse nonsteroidal anti-inflammatory drugs has been shown to be accompanied by histological and molecular changes that are responsible for this beneficial effect. The objective of the present work was to analyze the histological changes caused by meclofenamic acid in androgen-independent prostate cancer. Tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In addition, other COX enzyme inhibitors such as Ibuprofen and celecoxib did not affect IL-1β release (Daniels et al, 2016). These fenamic acid derivatives have been studied in a variety of disease models including AD, prostate cancer, and more (Delgado-Enciso et al, 2015;Mangan et al, 2018).…”
Section: Fenamic Acidsmentioning
confidence: 99%
“…In addition, other COX enzyme inhibitors such as Ibuprofen and celecoxib did not affect IL-1β release (Daniels et al, 2016). These fenamic acid derivatives have been studied in a variety of disease models including AD, prostate cancer, and more (Delgado-Enciso et al, 2015;Mangan et al, 2018).…”
Section: Fenamic Acidsmentioning
confidence: 99%
“…Recent studies demonstrated that targeting the phosphatidylinositide 3-kinase (PI3K)/AKT signaling pathway is a major strategy for treating androgen-independent PCa [74] or alternately meclofenamic acid can be prescribed. Meclofenamic acid is a nonsteroidal anti-inflammatory drug that has shown therapeutic potential for different types of cancers, including androgen-independent PCa [75]. The time point for intervention application was suggested to be at the point when the level of prostate-specific antigen retrogrades.…”
Section: Bioenergetic Profile Of Rmcs Affected By Bicmentioning
confidence: 99%
“…Meclofenamic acid (MA), an NSAID, has been shown to have anti-carcinogenic effects on various types of cancer. [9][10][11]20 However, the effect of the drug on LNCaP cell migration and invasion has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…8 Meclofenamic acid (MA), a nonsteroidal antiinflammatory drug (NSAID), has been shown to have anticarcinogenic effects in addition to its anti-inflammatory properties. [9][10][11][12][13] It has been shown that MA inhibited the growth of several cancer types including uterine cervical cancer and bladder cancer. However, it was realized that there is no study investigating the role of MA on androgen-dependent PC.…”
Section: Introductionmentioning
confidence: 99%